ANALISIS KESIAPAN GURU IPA DALAM IMPLEMENTASI KURIKULUM 2013 DI SMP NEGERI SE- KECAMATAN STABAT - Safitri, Layil (STKIP Andi Matappa Pangkep, 2018)
The study of Science Teacher Readiness Analysis in 2013 Curriculum Implementation in this Public Middle School aims to find out: the readiness of Junior High School science teachers in preparing learning by implementing the 2013 curriculum and the readiness of junior high school science teachers in preparing learning tools by implementing the 2013 curriculum. The subjects in this study were 2 teachers Stabat 1 state junior high school, 4 Stabat state 2 junior high school teachers, and 5 Stabat state 5 junior high school teachers. This type of research is quantitative descriptive analysis research. The results showed that: State Junior High School Teachers in Stabat Subdistrict were declared ready in preparing the 2013 curriculum learning, this can be seen from the average percentage of 79% with the ready category; State Junior High School Teachers in Stabat Subdistrict are in the ready category in preparing the 2013 curriculum learning tools, this can be seen from the following data: Average percentage of readiness of Stabat 1 Public Middle School teachers is 79% with ready category. The average percentage of readiness of Stabat 2 state junior high school teachers is 70% in the ready category.